Intervensi Non – Farmakologi melalui Cognitive Stimulation Therapy dalam Peningkatan Fungsi Kognitif pada Lansia dengan Demensia - Indah Millenia Ratnasari; Witdiawati Witdiawati; Mamat Lukman (Universitas Malahayati Lampung, 2025)
ABSTRACT Elderly individuals, categorized as those at the age 60 years or older, often begin to experience a decline in bodily functions such as dementia. Dementia is a condition commonly encountered in the elderly, characterized by symptoms such as a decline in both short-term and long-term memory, impaired cognitive processes compared to their younger years, disruptions in daily activities, and diminished intellectual, cognitive, and personality capacities. One therapy that can be implemented to enhance cognitive function in the elderly is Cognitive Stimulation Therapy. The purpose of this case report is to examine the effects of Cognitive Stimulation Therapy in improving cognitive function in elderly individuals with dementia. This research method uses a case report approach with nursing care for elderly individuals with dementia by intervention of Al-Qur'an reading exercises administered over a period of 14 days. Following the implementation of Cognitive Stimulation Therapy through reading exercises, the client showed some improvement in recalling events and remembering the content that had been read. During the Cognitive Stimulation Therapy program, there was stimulation of cognitive function in the patient, leading to an improvement in cognitive abilities. Cognitive Stimulation Therapy can be used by nurses as a therapeutic intervention for elderly patients with dementia. Keyword: Cognitive Stimulation Therapy, Dementia, Elderly ABSTRAK Lansia merupakan individu yang dikategorikan pada usia sama atau lebih dari 60 tahun, yang pada saat usia inilah individu mulai merasakan fungsi tubuh yang berkurang fungsinya. Demensia adalah suatu kejadian yang dialami oleh individu dengan lanjut usia, hal tersebut terjadi dengan beberapa gejala yaitu menurunya memori jangka pendek dan panjang, proses berfikir yang tidak lagi sama ketika masih muda, terganggunya kemampuan aktivitas sehari-hari, hingga terganggunya kapasistas intelektual serta kognitif dan kepribadian individu. Salah satu terapi yang dapat dilakukan untuk meningkatkan fungsi kognitif pada lansia adalah Cognitive Stimulation Therapy. Tujuan dari laporan kasus ini adalah untuk mengetahui pengaruh Cognitive Stimulation Therapy dalam meningkatkan fungsi kognitif pada lansia dengan demensia. Metode penelitian ini menggunakan metode laporan kasus pendekatan asuhan keperawatan dengan lansia dengan demensia, diberikan intervensi latihan membaca Al – Qur’an selama 14 hari. Setelah dilakukan Cognitive Stimulation Therapy menggunakan metode membaca, pasien dapat sedikit mengingat peristiwa yang dihadapi serta mengingat bacaan-bacaan yang sudah dibaca. Pada saat program Cognitive Stimulation Therapydilakukan terjadi rangsangan pada fungsi kognitif lansia sehingga terjadilah peningkatan fungsi kognitif. IntervensiCognitive Stimulation Therapy dapat digunakan oleh perawat sebagai terapi pada lansia dengan demensia. Kata Kunci: Cognitive Stimulation Therapy, Demensia, Lansia